Alpha-amylase inhibitory activity of inhibitor proteins in different types of commercial rice - Ramli, Nur Syazila; Md Zin, Noor Hasniza (Zebline International Publishing, 2018)
The inhibition of α-amylase enzyme by the inhibitor proteins extracts of all the three types of commercial rice, white rice (WR), brown rice (BR) and glutinous rice (GR) were investigated. Among the three types of rice, the BR has significantly the highest concentration of the inhibitor protein (0.030 ± 0.002 mg/ml) compared to glutinous rice (0.006 ± 0.001 mg/ml) and white rice (0.005 ± 0.001 mg/ml). In term of the percentage of inhibition of the α- amylase enzyme of the Aspergillus oryzae, the brown rice shows the highest inhibition (61.22 %) among the three types of rice with the lowest maltose liberated. The acarbose (0.1 mg/ml) which was used as a positive control represent the highest inhibition of the α-amylase enzyme inhibitor among all of the tested samples. Even though inhibitor protein extract of BR is possessed lower ability to inhibit the α-amylase, yet it still can be one of the best option and alternative for the Diabetes Mellitus patients for their daily consumption compared to the WR and GR.